THEORITICAL VIEWS ON THE PHENOMENON OF SYMMETRY AND ASYMMETRY IN WORLD LINGUISTICS (Universal International Scientific Journal, 2026)
This article analyzes the theoretical interpretation of symmetrical and asymmetricalphenomena in linguistics and their role in the language system. The study analyzes the relationshipbetween form and content between linguistic units, their compatibility or incompatibility. It is shownthat symmetry expresses a balanced, harmonious relationship between form and content in thelanguage system, while asymmetry manifests itself in such phenomena as disproportion, ambiguity,synonymy and homonymy between them
Keywords: symmetry; asymmetry; cognitive activity